Expanding, Opening and Pluralizing: New Diplomatic History as a Comprehensive Approach - Schnicke, Falko (Österreichische Zeitschrift für Geschichtswissenschaften, 2024)
In recent decades, diplomatic history has undergone a significant evolution, marked by a turn towards more inclusive methodologies and interdisciplinary approaches. This shift, often referred to as New Diplomatic History (NDH), seeks to explore not only the outcomes but also the intricate processes and practices of diplomatic interactions. It goes beyond the traditional focus on government actors and formal negotiations to investigate the activities of further agents, cultural dynamics, and transnational networks, thus encompassing less-researched sites of diplomacy. As scholars increasingly recognize the complexities of international relations, this burgeoning field offers a rich tapestry of narratives that challenge previous diplomatic histories and offer fresh insights. All of this is intended to help achieve an understanding of diplomacy that is less essentialist and more functional.